2015
DOI: 10.1007/s13726-015-0352-1
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline and polypyrrole/TiO2 nanocomposite coatings on Al1050: electrosynthesis, characterization and their corrosion protection ability in saltwater media

Abstract: PPy (PE = 94.9 %) and uncoated Al1050 electrodes. These nanocomposites can be used in airplanes, space technology, automobiles, electronics, and building sectors, as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 35 publications
(32 reference statements)
0
8
0
1
Order By: Relevance
“…Corrosion and wear performance have also been improved by the use of NiTi coating modified with ZrO 2 coatings on AISI 316 SS [22] by using a cold spray technology (a coating process in which a metal substrate is exposed to small particles (1 to 50 µm), which are accelerated by the supersonic flow of compressed gas at a high speed (300-1200 m/s)). The process is based on a combination of particle temperature, speed and size to allow spraying at the lowest possible temperature to: coat the cobalt chromium (Co-Cr) alloy L605 powders in order to improve the corrosion resistance and the strength of 316L SS [23]; Pd-Ni/Pd-Cu double coating on the 316SS surface by electroplating [24]; nanocomposite coatings of polychlorotrifluoroethylene (PCTFE) particles with nickel-tungsten (Ni-W) coatings through the electro deposition procedure [25]; polymerized vinyltrimethoxysilane (PVTMS) coating with henna's aqueous solution forming a PVTMS/henna hybrid sol-gel for biomedical applications [26]; polyaniline-graphene nanocomposite coatings electrodeposited on 310 SS by cyclic voltammetry technique [27]; and synthesis of polyaniline-montmorrilonite nanocomposite coatings deposited on 316L SS by electrodeposition [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion and wear performance have also been improved by the use of NiTi coating modified with ZrO 2 coatings on AISI 316 SS [22] by using a cold spray technology (a coating process in which a metal substrate is exposed to small particles (1 to 50 µm), which are accelerated by the supersonic flow of compressed gas at a high speed (300-1200 m/s)). The process is based on a combination of particle temperature, speed and size to allow spraying at the lowest possible temperature to: coat the cobalt chromium (Co-Cr) alloy L605 powders in order to improve the corrosion resistance and the strength of 316L SS [23]; Pd-Ni/Pd-Cu double coating on the 316SS surface by electroplating [24]; nanocomposite coatings of polychlorotrifluoroethylene (PCTFE) particles with nickel-tungsten (Ni-W) coatings through the electro deposition procedure [25]; polymerized vinyltrimethoxysilane (PVTMS) coating with henna's aqueous solution forming a PVTMS/henna hybrid sol-gel for biomedical applications [26]; polyaniline-graphene nanocomposite coatings electrodeposited on 310 SS by cyclic voltammetry technique [27]; and synthesis of polyaniline-montmorrilonite nanocomposite coatings deposited on 316L SS by electrodeposition [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of 0.03% Ti in the obtained values indicates that TiO 2 is present in the nanocomposite structure. Ates et al found that the amount of Ti in the polypyrrole-TiO 2 [21] and Poly (N-methylpyrrole) TiO 2 [29] nanocomposites synthesized on the aluminum surface in oxalic acid solution were 0.07% and 0.04%, respectively. Figure 7 shows Nyquist diagrams for CS, CS/ZnNi, CS/ZnNi/ POA and CS/ZnNi/POA-TiO 2 electrodes after 2 and 96 h of exposure time in 3.5% NaCl corrosive solution.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Jafari et al [20] stated that POA-TiO 2 nanocomposite synthesized on the aluminum surface in 0.5 M oxalic acid solution significantly reduced the corrosion rate of aluminum. Ates et al [21] coated polyaniline-TiO 2 and polypyrrole-TiO 2 nanocomposites on the aluminum surface and found that protective properties of the nanocomposites were better than polymer coatings. Radhakrishnan et al [22] synthesized polyaniline-TiO 2 nanocomposite and found that the presence of nano TiO 2 had an important role in corrosion prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The peak observed at 1457 cm −1 is related to the antisymmetric stretching vibration in the PPy ring. The bands at 1200 and 790 cm −1 reveal the presence of C C. The peak at 1123 cm −1 can be assigned to the C H in the plane vibration band [24,33].…”
Section: Photoelectrochemical Measurementsmentioning
confidence: 98%